2013
DOI: 10.1007/s10472-013-9376-4
|View full text |Cite
|
Sign up to set email alerts
|

The dark side of interval temporal logic: marking the undecidability border

Abstract: Unlike the Moon, the dark side of interval temporal logics is the one we usually see: their ubiquitous undecidability. Identifying minimal undecidable interval logics is thus a natural and important issue in that research area. In this paper, we identify several new minimal undecidable logics amongst the fragments of Halpern and Shoham’s logic HS, including the logic of the overlaps relation, over the classes of all finite linear orders and all linear orders, as well as the logic of the meets and subinterval r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2
2

Relationship

7
1

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…The satisfiability problem for HS turns out to be highly undecidable for all relevant (classes of) linear orders [11]. The same holds for most fragments of it [3,13,18]. However, some meaningful exceptions exist, including the logic of temporal neighbourhood AA and the logic of sub-intervals D [4][5][6]24].…”
Section: Introductionmentioning
confidence: 99%
“…The satisfiability problem for HS turns out to be highly undecidable for all relevant (classes of) linear orders [11]. The same holds for most fragments of it [3,13,18]. However, some meaningful exceptions exist, including the logic of temporal neighbourhood AA and the logic of sub-intervals D [4][5][6]24].…”
Section: Introductionmentioning
confidence: 99%
“…In [8], it has been shown that the satisfiability problem for HS interpreted over all relevant (classes of) linear orders is highly undecidable. Since then, a lot of work has been done on satisfiability for HS fragments, which showed that undecidability rules over them [3], [10], [13]. However, meaningful exceptions exist, e.g., the interval logic of temporal neighbourhood AA and the logic of sub-intervals D [4]- [6], [17].…”
Section: Introductionmentioning
confidence: 99%
“…(Actually, the three Allen's modalities meets A, started-by B, and finished-by E, together with the corresponding inverse modalities A, B, and E, suffice for expressing the entire set of relations.) The satisfiability problem for HS is undecidable over all relevant classes of linear orders [13], and most of its fragments (with meaningful exceptions) are undecidable as well [8,19].…”
Section: Introductionmentioning
confidence: 99%